Influence of Abiotic Factors Temperature and Water Content on Bacterial 2-Chlorophenol Biodegradation in Soils - Moxley, Ellen; Puerta-Fernández, Elena; Gómez, Enrique J.; Gonzalez, Juan M. (Frontiers in Environmental Science, 2019)
Halogenated compounds are environmental pollutants toxic to humans and wildlife. Certain microorganisms degrade these halogenated compounds. However, little is known about the potential of microorganisms in bioremediation under extreme conditions, specifically in arid and semi-arid soils frequently exposed to high temperatures and desiccation periods. Arid and semi-arid environments and deserts make up vast areas of Earth’s landmass. To investigate the degradation of 2-chlorophenol (2-CP) in soils as a function of temperature and water availability, three bacterial species were tested, two soil mesophiles of the genus Rhodococcus, R. opacus and R. erythropolis, and a soil thermophilic isolate, Parageobacillus thermoglucosidasius. Degradation trials in soil samples with these species were performed over a range of water activity from 1 to 0.4. At their optimum growth temperature, R. opacus showed maximum 2-CP degradation at water activity 0.9 sharply decreasing when lowering water activity. Nevertheless, the Parageobacillus isolate (optimum growth temperature 60ºC) showed maximum 2-CP degradation rates at water activity 0.5 which represented highly desiccating conditions. Parageobacillus degradation of 2-CP was very low at water activity above 0.9. Thus, biodegradation of 2-CP in soils is possible even under arid conditions although different microbial species might be involved in this task depending on the interactions of abiotic factors and the diversity of microbial communities in soils. These results contribute to understand the potential biodegradation of specific halogenated compounds in the environment which is of great relevance to comprehend the fate of halogenated pollutants (i.e., 2-CP) in deserts, arid and semi-arid soils.